Answer:
36 g^2 + -60 g h + 25 h^2 thus: B
Explanation:
Expand the following:
(6 g - 5 h)^2
(6 g - 5 h) (6 g - 5 h) = (6 g) (6 g) + (6 g) (-5 h) + (-5 h) (6 g) + (-5 h) (-5 h):
6×6 g g - 5×6 g h - 5×6 h g - 5 (-5) h h
6 g×6 g = 6×6 g^2:
6×6 g^2 - 5×6 g h - 5×6 h g - 5 (-5) h h
6×6 = 36:
36 g^2 - 5×6 g h - 5×6 h g - 5 (-5) h h
6 (-5) = -30:
36 g^2 + -30 g h - 5×6 h g - 5 (-5) h h
-5×6 = -30:
36 g^2 - 30 g h + -30 h g - 5 (-5) h h
-5 h (-5) h = -5 (-5) h^2:
36 g^2 - 30 g h - 30 h g + -5 (-5) h^2
-5 (-5) = 25:
36 g^2 - 30 g h - 30 h g + 25 h^2
g h (-30) + h g (-30) = -60 g h:
Answer: 36 g^2 + -60 g h + 25 h^2